REPERE EPISTEMOLOGICE DE DEFINIRE A VALORILOR - Angela TULEI (Moldova State University, 2019)
În articol problema privind valorile este abordată din diferite perspective. Istoria omului începe odată cu istoria semnelor şi a valorilor. Animalele, spre deosebire de om, fiind necuvântătoare, nu pot să-şi transforme atracţiile şi repulsiile în valori. Numai dialogul, mai întâi cu ceilalţi şi mai târziu cu sine însuşi, permite distanţarea de fenomene şi ivirea întrebărilor despre esenţa lor. Numai dialogul face posibilă elaborarea ideilor, singurul mijloc dialogal de comunicare fiind limbajul uman. Teoria valorilor reprezintă o serie de abordări pentru a înțelege cum, de ce și în ce măsură oamenii dau valoare lucrurilor. Chestiunea valorilor a fost definită din diverse perspective și dimensiuni, cum ar fi: dimensiunea filosofică, perspectiva istorică, perspectiva economică, pedagogică, estetică, psihologică etc., însă cercetările arată că conceptul valoare capătă ecou mai cu seamă în reflecția pedagogică. EPISTEMOLOGICAL GUIDELINES OF DEFINING VALUES This article deals with the definition of values from various perspectives. Human history begins with the history of signs and values. Animals, unlike humans, being unable to speak, cannot turn their attractions and repulsions into values. Only the dialogue, at first with the others and later with one's own self, allows detachment from phenomena and raises questions about their essence. Only the dialogue makes it possible to develop ideas, the only means of dialogic communication being the human language. Axiology is the study of the nature of value and valuation, and of the kinds of things that are valuable; it refers to a series of approaches to understand how, why, and to what extent things are valuable for people. The question of values has been defined from various perspectives and dimensions, such as: the philosophical dimension, the historical, economic, pedagogical, aesthetic, psychological perspectives, etc., but research shows that the concept of value is specially echoed in the pedagogical reflection.